Form and function of the teleost lateral line revealed using three-dimensional imaging and computational fluid dynamics. Issue 130 (31st May 2017) - Herzog, Hendrik; Klein, Birgit; Ziegler, Alexander
Abstract : Fishes sense weak water motion using the lateral line. Among the thousands of described fish species, this organ may differ in size, shape and distribution of individual mechanoreceptors or lateral line canals. The reasons for this diversity remain unclear, but are very likely related to habitat preferences. To better understand the performance of the organ in natural hydrodynamic surroundings, various three-dimensional imaging datasets of the cephalic lateral line were gathered using Leuciscus idus as representative freshwater teleost. These data are employed to simulate hydrodynamic phenomena around the head and within lateral line canals. The results show that changes in canal dimensions alter the absolute stimulation amplitudes, but have little effect on the relation between bulk water flow and higher frequency signals. By contrast, depressions in the skin known as epidermal pits reduce bulk flow stimulation and increase the ratio between higher-frequency signals and the background flow stimulus.